Deformation and vibration analysis of compressor rotor blades based on fluid-structure coupling. (April 2021) - Sun, Hai'ou; Ren, Aoyu; Wang, Yanhua; Zhang, Mingfei; Sun, Tao
Highlights: Rotor deformation and vibration under different materials were investigated. Centrifugal loading is the main reason for the increase of natural frequency. The frequency increase range is very small compared to the first natural frequency. Abstract: Under the influence of aerodynamic and rotational load, deformation and vibration could occur to rotor blades of axial compressor, which may cause fatigue fracture, and threaten the exist of tip clearance because it is the assurance of operation safety by separating the rotor from the case. The overall performance will be deteriorated by the change of blade shape due to the deformation and vibration. Three different materials, titanium alloy, aluminum alloy and stainless steel are compared quantitatively under various operating conditions by fluid-structure coupling method. First the CFD method is validated by experimental data, the obtained pressure distribution on blade surface is exerted to the structure as boundary condition, then deformation characteristic and the corresponding maximum equivalent stresses are analyzed, at last vibration modal is analyzed and resonance points, the main reason for the vibration-induced failure, are predicted by Campbell diagrams. The results show that deformation increases with rotation speed and outlet pressure; the aluminum alloy has the largest deformation of the three materials. The equivalent stress of the blade is mainly caused by rotation, large stress regions are often near the blade root. The tip clearance of rotor blades can be reduced by deformation in the radial direction, for titanium and aluminum alloy blade, the maximum stretched length of blade at 100% rotation can account for 30% of the designed tip clearance. Centrifugal loading is the main reason for the increase of natural frequency while the increased amplitude with rotation speed is extremely small compared to the first order natural frequency.